PERANAN KEPALA DESA DALAM PENYELESAIAN PERSELISIHAN HUKUM ANTAR WARGA DESA - Aspani, Budi (Faculty of Law, University of Palembang, 2018)
Village Government consists of Village Head and Village Device as regulated in the above mentioned village law. That one of the duties and responsibilities of the Village Head is to reconcile the rural community disputes. The type of research used is empirical legal research and by using primary, secondary, and non-legal legal materials. The legal material can then be analyzed qualitatively. Qualitative analysis is done by describing the data generated in the form of explanations or descriptions of sentences to answer the subject matter. The results obtained that: The Village Head acts as a mediator and guided by deliberation to consensus. Disputes that can not be settled then both parties are handed over to the authorities or the authorities. Inhibiting Factors Lack of knowledge of the villagers of Parit about the role of village heads in settling disputes between citizens; The unambiguous provisions of the law on paradigms or models of disputes and disputes to be resolved by the Village Head; The community sometimes considers that if he reports or resolves through the village level, it means making a disgrace of himself in his neighborhood. Pushing Factors Starting the growing level of public awareness to create a safe and orderly environment in Parit Village; The Parit Village community is a homogeneous society so that people's tolerance is very good